PELATIHAN INOVASI PEMASARAN DIGITAL DAN LITERASI KEUANGAN DALAM MENINGKATKAN POTENSI UMKM BOJONG JENGKOL BOGOR - Suryowati, Budi; Harianti, Ati; Syihab, Faizah; Puspita, Nelly Camelia; Haikal, Muhammad; Yolanda, Yolanda (Institut Teknologi dan Bisnis Swadharma, 2024)
Community service is a tangible effort to apply science and technology to directly benefit society. In the context of training Micro, Small, and Medium Enterprises (MSMEs) based on digital marketing with the theme